Preliminary assessment of the clinical effects of lecanemab following 18 months of treatment in the open label extension of the phase 2 proof of concept study, BAN2401‐G000‐201, in subjects with early Alzheimer's disease. (31st December 2021) - Swanson, Chad J; Dhadda, Shobha; Irizarry, Michael C; Kanekiyo, Michio; Li, David JianJun; Kaplow, June; Gordon, Robert; Heanue‐Travers, Helena; Hodgkinson, Mark; Kramer, Lynn D
Abstract: Background: Lecanemab (BAN2401) is a humanized IgG1 monoclonal antibody that preferentially targets soluble aggregated Aβ species (oligomers, protofibrils) and insoluble fibrils. Lecanemab reduced amyloid and slowed clinical decline in an 18‐month Phase 2 proof of concept study in early Alzheimer's disease (Alz Res Therapy 13; 2021). An Open label extension (OLE) with 10 mg/kg IV biweekly lecanemab dosing was implemented after analysis of the Core study, with an intervening gap period off‐treatment ranging from 9‐54 months (mean 24 months). The present study assesses longitudinal clinical status (CDR‐SB, ADAS‐cog, ADCOMS) for subjects completing the Core and 18 months of treatment in OLE. Method: At entry into the core study, subjects were required to have early AD (amyloid positive) with global CDR of 0.5 or 1. MMRM analyses modeled clinical scales across the Core, variable gap period off lecanemab, and the OLE period. Analyses were stratified based on subjects who were: (1) global CDR ≤1 at OLE baseline; or (2) who had progressed beyond the early AD stage to CDR global >1 by OLE baseline. Result: In subjects with global CDR ≤1 at OLE baseline, lecanemab treatment differences relative to placebo observed after 18 months of treatment in the Core were maintained at a 3 month (off drug) follow‐up visit and at the end of the gap period (OLE baseline). In the gap period, the rates of progression were similar between those treated with lecanemab and placebo in the core period. Clinical progression in the OLE appeared to plateau with lecanemab treatment among those who were global CDR ≤1 at the OLE baseline, while those who were global CDR >1 continued to progress. Conclusion: Clinical data from the gap period suggest that subjects may need continued treatment with lecanemab, even though amyloid PET and plasma biomarker findings indicate amyloid has been removed. Apparent differences in clinical progression between those with global CDR ≤1 and those with global CDR >1 suggest the hypothesis that early AD subjects may be more likely to benefit from treatment. These concepts will be further explored in ongoing Phase 3 lecanemab clinical trials.